Lithiophilic Ag/Li composite anodes via a spontaneous reaction for Li nucleation with a reduced barrier. Issue 36 (3rd September 2019) - Liu, Tiancheng; Hu, Qiyang; Li, Xinhai; Tan, Lei; Yan, Guochun; Wang, Zhixing; Guo, Huajun; Liu, Yong; Wu, Yuping; Wang, Jiexi
Abstract : Lithiophilic silver/lithium composite anodes are synthesized via a spontaneous displacement reaction to settle the problems of lithium metal anodes by regulating Li nucleation and homogenizing Li-ion flux. Abstract : Infinite volume expansion and high reactivity severely hinder the commercial applications of lithium metal batteries. Moreover, the short circuit caused by Li dendrites is fatal for the long-term performance of lithium metal batteries and may cause safety problems. Herein, lithiophilic silver/lithium (Ag/Li) composite anodes are synthesized via a spontaneous displacement reaction between silver nitrate and Li foil at room temperature, which can settle the above challenges by regulating Li nucleation and homogenizing Li-ion flux. Benefiting from the lithiophilic design, Li ion realizes zero nucleation overpotential on the as-obtained Ag/Li anodes with abundant spherical silver nanoparticles. Additionally, the by-product, lithium nitrate, acts as an electrolyte additive, which further ensures uniform Li deposition. Consequently, Ag/Li symmetric cells demonstrate ultralong lifespan with repeated plating/stripping for 1000 cycles at the current densities of 1 mA cm −2 and 5 mA cm −2, with negligible voltage fluctuations. Furthermore, the full-cell devices, paired with LiFePO4, also exhibit excellent electrochemical performance. The facile and effective strategy provides a promising prospect for commercial applications of lithium metal batteries.